Upper- and lower-limb muscular fatigue during the 200-m front crawl - Figueiredo, P.; Rouard, A.; Vilas-Boas, J. P.; Fernandes, R. J. (Applied Physiology, Nutrition, and Metabolism, 2013)
The aim of this study was to investigate how upper- and lower-limb muscle fatigue evolves in a 200-m front crawl swimming race. Surface electromyography signals were collected from the flexor carpi radialis, biceps brachii, triceps brachii, pectoralis major, upper trapezius, tibialis anterior, biceps femoris, and rectus femoris muscles of 10 international-level swimmers; 4 underwater cameras were used for kinematic analysis. In addition, blood lactate was measured before and after the test using capillary blood samples. Swimming speed and stroke length decreased from the beginning to the end of the effort, whereas stroke frequency increased after an initial decrease to maintain speed. Concomitant with the decrease in speed, blood lactate increased to 11.12 (1.65) mmol/L. The changes in stroke parameters were associated with an increase in integrated electromyography (20%-25%) and a decrease in spectral parameters (40%-60%) for all of the upper-limb muscles, indicating the reaching of submaximal fatigue. The fatigue process did not occur regularly during the 8 laps of the 200 m but was specific for each muscle and each subject. Lower-limb muscles did not present signals of fatigue, confirming their lower contribution to swimming propulsion. The test was conducted to individualize the training process to each muscle and each subject.